University teaching practices and French classroom representations: a changing reality - TOBAL, Ismahane; DAKHIA, Abdelouahab (Journal of Human Sciences, 2021)
Our study is intended to reflect on teaching practices in the French class at the Algerian university; it is a question of this professorial action underpinned by the active methodology tending towards responsible learning practices in the sense of the autonomy of the learner who supports himself. To do this, all action will be part of an active methodology understood as a heterogeneous set of knowledge, rules, actions, activities, plural know-how. Therefore, our problem relates to this praxis in French class and especially to the representations representing the catalyst of the whole process of teaching and learning. Thus, teachers and learners, build their ethos in relation to an ethic of partners in pedagogical communication dependent on cognitive didactics of languages. "It is these values ​​and principles specific to the teacher and the learning being that we perceive through the values ​​and principles of Others in any organized and interested exchange"[1]